2008
DOI: 10.1095/biolreprod.107.062901
|View full text |Cite
|
Sign up to set email alerts
|

Immunocytochemical and Ultrastructural Analyses of the Function of the Ubiquitin-Proteasome System During Spermiogenesis with the Use of the Inhibitors of Proteasome Proteolytic Activity in the Alga, Chara vulgaris1

Abstract: Spermiogenesis in Chara vulgaris and in animals share many common features, including exchange of nucleohistones into nucleoprotamines, remodeling and extreme condensation of chromatin, formation of flagellae and of microtubule manchette, and decrease in cytoplasm volume. In C. vulgaris, spermiogenesis is not preceded by meiosis since this alga is a haplobiont. In the present work we showed that in early spermiogenesis characterized by a significant metabolic activity of spermatids, the inhibitors of proteasom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
1
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 52 publications
0
13
1
1
Order By: Relevance
“…In mammals, Wnt/β-catenin pathway has been shown to be crucial for ovarian differentiation, and β-catenin , is considered as a female-like gene [ 48 ]. In teleosts such as rainbow trout and zebrafish, studies have also implicated Wnt/β-catenin signaling pathway in gonad differentiation [ 49 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…In mammals, Wnt/β-catenin pathway has been shown to be crucial for ovarian differentiation, and β-catenin , is considered as a female-like gene [ 48 ]. In teleosts such as rainbow trout and zebrafish, studies have also implicated Wnt/β-catenin signaling pathway in gonad differentiation [ 49 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ctnnb1 is another female-like gene with a critical function in female differentiation in mammals, antagonizing sox9 and blocking testis development, thus promoting ovarian development [ 68 ]. Ctnnb1 is the key downstream component of the canonical wnt signaling pathway and our results are in agreement with a conserved female function of this pathway, which has also been shown in zebrafish [ 69 ] and rainbow trout [ 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among the genes which presented sex dependent temperature effects, ctnnb1 , piwi2 , sf1 and sox6 showed higher expression at low temperatures in males. Among these, ctnnb1 is remarkable because it not only occupies a downstream position in the wnt pathway [ 87 ], which needs to be up-regulated for the development of an ovary in zebrafish [ 68 ], but also because it showed temperature-dependent expression differences in our study at 90 dpf, the onset of SD. Genes found upstream in the wnt signalling pathway are likely regulated by temperature and responsible for this increase in ctnnb1 expression in turbot.…”
Section: Discussionmentioning
confidence: 99%
“…Bromodomains bind acetylated lysines, which are present in various proteins i.e., histones playing an important role in chromatin organization during spermiogenesis [27]. The results of previous immunofluorescent and ultrastructural analyses showed that blocking the removal of histones, during the exchange of these proteins into protamines, hindered the proper course of spermiogenesis [3,28]. The studies of spermatogenesis concerning Brdt gene in two fish species, which have different methods of nuclear protein exchange, revealed variations in this gene expression which could indicate a different role of Brdt protein [29].…”
Section: Introductionmentioning
confidence: 99%